3-D Classification of Stock Marketsand Its Using for Evaluation of the Financial Analysis Methods Applicability - Siniavskaya, Olga A.; Zhelezko, Boris A. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
In the article stock markets peculiarities are investigated, which define acceptability of different decision support methods in stock trading (technical analysis, fundamental analysis, indicators). Existing approaches to stock market classification and clusterization are considered, their shortcomings are shown. Authors’3-D classification of stock markets is offered, on the base of the following criteria: stock market activity, stock market age, economy development level, information transparency. Conditions of the applicability of technical analysis, indicators and fundamental analysis were evaluated by means of the suggested classification.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 135-141